Percutaneous peritoneal drainage in isolated neonatal gastric perforation - Aydin, Mustafa; Deveci, Ugur; Taskin, Erdal; Bakal, Unal; Kilic, Mehmet (Baishideng Publishing Group Inc, 2015)
A comment on the article by He et al, Idiopathic neonatal pneumoperitoneum with favorable outcome: A case report and review, published on World Journal of Gastroenterology that reported a case of idiopathic neonatal pneumoperitoneum, possibly due to gastric perforation, with a favorable outcome without surgical intervention.
Keywords: Pneumoperitoneum; Gastric perforation; Intestinal perforation; Conservative management; Percutaneous peritoneal drainage; Antibiotic; Newborn infant